Medication Error in Anaesthesia A Review - Mondal, Montosh Kumar; Roy, Beauty Rani; Banik, Shibani; Banik, Debabrata (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Medication error is a major cause of morbidity and mortality in medical profession . There is an increasing recognition that medication errors are causing a substantial global public health problem, as many result in harm to patients and increased costs to health providers.Anaesthesia is now safe and routine, yet anaesthetists are not immune from making medication errors and the consequences of their mistakes may be more serious than those of doctors in other specialties. Steps are being taken to determine the extent of the problem of medication error in anaesthesia. In this review, incidence, types, risk factors and preventive measures of the medication errors are discussed in detail. Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 31-35